Identifikasi Bakteri Pelarut Kalium Indigenus Asal Perkebunan Nanas - Kusuma Handayani; Mirawanty Amin (Institut Pertanian Bogor, 2024)
The use of relatively high doses of inorganic fertilizers to increase yields in plantation-scale pineapple (Ananas comosus) cultivation can lead to new problems, such as being toxic to plants, polluting the environment, and increasing production costs. The utilization of rhizosphere microbes, such as potassium solubilizing bacteria (KSB) is expected can reduce the dose of inorganic K fertilizer application because it can dissolve potassium-fixed Al and Fe soil so that it is available to plants. This study aims to assess and characterize the potential of BPK in pineapple plantation areas. KSB evaluation was carried out based on the Potassium Solubility Index (IKK), besides that, it also carried out the characterization of bacteria that have the potential as CPC isolates. CPC was isolated from planting blocks with low and high production levels in the vegetative (V) and generative (G) phases with 5 replications. As many as 20 isolates from the CPC population on pineapple plantations were successfully isolated in this study. The lowest K solubility index of 0.6 was obtained in isolate RV1 and the highest, namely 1.2 in isolate RG1. Among these isolates, RG1 is Gram-positive and grows optimally at pH 5, temperature 30°C. Based on the results of the phylogenetic analysis, it is known that this potassium solubilizing isolate has the same level of similarity with the bacterium Bacillus subtilis. Keywords: Bacillus, indigenous, potassium, solubilizing index, temperature